Effect of hydrostatic pressure on structural and electronic properties of TGS crystals (first-principle calculations) - Andriyevsky, B.; Ciepluch-Trojanek, W.; Patryn, A. (Condensed Matter Physics, 2007)
First principle calculations of the effect of hydrostatic pressure on the structural and electronic parameters of TGS crystals have been carried out within the framework of density functional theory using the CASTEP code. The volume dependence of total electronic energy E(V) of the crystal unit cell satisfies the third-order Birch-Murnaghan isothermal equation of state. For the pressure range of −5 . . . 5 GPa, the bulk modulus was found to be equal to K = 45±5 GPa. The relative pressure changes of the unit cell parameters were found to be linear in the range of −5 . . . 5 GPa. Crossing of the pressure dependencies of enthalpy corresponding to the ferroelectric and non-ferroelectric phases at P = 7.7 GPa testifies to the probable pressure induced phase transition in TGS crystal.